2018
DOI: 10.1016/j.jecp.2017.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparing working memory in bilingual and monolingual Hispanic/Latino preschoolers with disruptive behavior disorders

Abstract: The current study examined differences in working memory (WM) between monolingual and bilingual Hispanic/Latino preschoolers with disruptive behavior disorders (DBDs). A total of 149 children (M = 5.10 years, SD = 0.53; 76% male) with elevated levels of DBDs, as indicated by their parents or teachers, were recruited to participate in an 8-week summer program prior to the start of kindergarten (Summer Treatment Program for Pre-Kindergarteners). Prior to the start of treatment, parents completed several measures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 86 publications
(84 reference statements)
0
8
0
Order By: Relevance
“…Additionally, with the help of being bilingual, children also show enhancement in their working memory (WM). Daubert and Ramani suggested that young bilinguals' enhanced working memory could be a positive influencer for mathematical development [8]. They compared 74 bilinguals and monolinguals by completing both non-verbal WM tests and metathetical tests involving addition, numeral identification and nonsymbolic magnitude comparison tasks [8].…”
Section: Working Memorymentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, with the help of being bilingual, children also show enhancement in their working memory (WM). Daubert and Ramani suggested that young bilinguals' enhanced working memory could be a positive influencer for mathematical development [8]. They compared 74 bilinguals and monolinguals by completing both non-verbal WM tests and metathetical tests involving addition, numeral identification and nonsymbolic magnitude comparison tasks [8].…”
Section: Working Memorymentioning
confidence: 99%
“…How bilingual individuals are different from monolinguals has been extensively studied, with a majority of researchers focusing on the better performance of bilinguals on tasks that measure certain cognitive abilities. Previous studies suggested that using two languages actively alters the executive functions, including inhibitory control and task shifting [5][6][7][8][9][10][11]. These cognitive abilities may be generalized to some non-linguistic domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, findings may be spurious, as Kaushanskaya and colleagues (2011) found similar results for monolinguals in comparison to both simultaneous bilinguals and native English late sequential learners of Spanish on an English short-term memory task, suggesting that no degree of bilingualism affected results, and that significant findings are likely due to some other variable. Moreover, research on working memory for verbal stimuli shows an equally muddy picture, with certain studies showing no difference (Buac et al, 2016;Danahy et al, 2007;Garcia, Ros, Hart, Graziano, 2018;Kohnert et al, 2006) and others showing a bilingual advantage (Kaushanskaya et al, 2014). However, these studies suffer from the same issues as mentioned for short-term memory.…”
Section: 2 T E S T S O F N O N -V E R B a L A B I L I T Ymentioning
confidence: 99%
“…Finally, research on several other domains has delivered consistent results, but the small number of studies suggests the need for repetition before any theories are made or conclusions are drawn from results. For example, a bilingual advantage for creativity in children (Galindo, 2012) and visuospatial working memory in both children (Garcia et al, 2018) and older adults (Padilla et al, 2016) have been reported. On the other hand, there was no difference found between monolingual and bilingual groups on a long-term memory task for real word (Padilla et al, 2016) or non-word lists , or on visual and auditory reaction time tests .…”
Section: 2 T E S T S O F N O N -V E R B a L A B I L I T Ymentioning
confidence: 99%